Chemical reactions between BaTiO3 ceramic and fluorine-containing atmosphere - Makovec, Darko (Acta chimica slovenica, 2002)
BaTi?$O_3$? ceramics were exposed to fluorine-containing atmosphere prepared by introducing a fluorination agent (?$CF_3CH_2OH?$) into a hot alumina-tube furnace. The fluorinated samples were studied using SEM and TEM. The fluorination resulted in the formation of a surface-reaction layer with a complex structure. At the reaction front fluorine reacts with BaTI?$O_3$? to produce ?$BaF_2$? and ?BaTi_2O_5$?. During the course of the fluorination the ?$BaTi_2O_5$? reacts further to produce ?$BaF_2$? and then subsequently Ba-polytitanates with an increasing content of titanium, and then finally ?$TiO_2$?. Fluorine also diffuses along the grain boundaries towards the pellet's interior. The presence of the fluorine stabilises the ?$BaTi_2O_5$? compound and consequently triggers its formation in the ceramic's interior in a reaction between ?$BaTiO_3$? and the intergranular phase ?$Ba_6Ti_{17}O_{40}$?.
Keywords: barijev titanat; ceramic; fluoriranje; kemijske reakcije; keramika